Cognitive dysfunction, elevated anxiety, and reduced cocaine response in circadian clock-deficient cryptochrome knockout mice - De Bundel, Dimitri; Gangarossa, Giuseppe; Biever, Anne; Bonnefont, Xavier; Valjent, Emmanuel (Frontiers in Behavioral Neuroscience, 2013)
The circadian clock comprises a set of genes involved in cell-autonomous transcriptional feedback loops that orchestrate the expression of a range of downstream genes, driving circadian patterns of behavior. Cognitive dysfunction, mood disorders, anxiety disorders and substance abuse disorders have been associated with disruptions in circadian rhythm and circadian clock genes, but the causal relationship of these associations is still poorly understood. In the present study, we investigate the effect of genetic disruption of the circadian clock, through deletion of both paralogs of the core gene cryptochrome (Cry1 and Cry2). Mice lacking Cry1 and Cry2 (Cry1-/-Cry2-/-) displayed attenuated dark phase and novelty-induced locomotor activity. Moreover, they showed impaired recognition memory but intact fear memory. Depression-related behaviors in the forced swim test or sucrose preference tests were unaffected but Cry1-/-Cry2-/- mice displayed increased anxiety in the open field and elevated plus maze tests. Finally, hyperlocomotion and striatal phosphorylation of extracellular signal-regulated kinase (ERK) induced by a single cocaine administration are strongly reduced in Cry1-/-Cry2-/- mice. Interestingly, only some behavioral measures were affected in mice lacking either Cry1 or Cry2. Notably, recognition memory was impaired in both Cry1-/-Cry2+/+ and Cry1+/+Cry2-/- mice. Moreover, we further observed elevated anxiety in Cry1-/-Cry2+/+ and Cry1+/+Cry2-/- mice. Our data indicate that beyond their role in the control of circadian rhythm, cryptochrome genes have a direct influence in cognitive function, anxiety-related behaviors and sensitivity to psychostimulant drugs.